Minor women novelists and their presentation of a feminine ideal, 1744-1800 - Spencer, J; Spencer, Jane (1982)
﻿ From the 1740s to 1800 there was a great increase both in the output of novels, and the number of women novelists. At the same time, an idealized view of femininity was prevailing in society. The relationship between these two features of eighteenth-century life helps us to assess the contribution of some eighteenth-century women to the development of the novel. In this period women's novels show some distinctive features, particularly in their portrayal of women. The idealized eighteenth-century view of women saw them as naturally virtuous, chaste, and full of the sensibility which was increasingly seen as an important positive quality. Therefore an idealized woman is the central figure in many sentimental novels. This idealized figure, used especially by women novelists, is of ambiguous significance. She raises women's status by demonstrating female superiority, but does so by modesty and submissiveness, qualities which eighteenth-century feminists perceived as inimical to women's emancipation. Women's novels often contain contradictions between explicit support of female emancipation, and idealized portraits of submissive heroines. Chapter 1 discusses the reasons for the rise of the woman novelist. Chapter 2 discusses her role and the reviewers' part in defining that role. Chapter 3 discusses women novelists in relation to feminism. The following chapters focus on particular writers. Sarah Fielding is a didactic writer with a certain feminist consciousness. The novels of Frances Brooke and Elizabeth Griffith epitomize the idealization of the heroine. The comic attack on the heroine is described with reference to Charlotte Lennox's work. The"relationship between sentimental- ism, didacticism and feminism is studied with reference to Clara Reeve and Harriet Lee. Chapter 8 introduces the 1790s, when politics dominates fiction and sentimentalism is attacked, and chapters on Jane West, Mary Wollstonecraft, and Charlotte Smith suggest the variety of women novelists' responses to these developments.